2009
DOI: 10.1111/j.1464-410x.2009.08399.x
|View full text |Cite
|
Sign up to set email alerts
|

Single‐port ‘scarless’ laparoscopic nephrectomies: the United Kingdom experience

Abstract: OBJECTIVE To present the UK experience to date with laparoendoscopic single‐site surgery (LESS) simple nephrectomy. PATIENTS AND METHODS Five female patients underwent LESS nephrectomy; three procedures were carried out with the umbilicus as the port of entry (U‐LESS). RESULTS All cases were completed uneventfully. The operative duration was 45–150 min and blood loss was negligible. There were no conversions to conventional multi‐port laparoscopy or open surgery. Recovery was uneventful with only minor complic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 27 publications
0
33
0
1
Order By: Relevance
“…In their initial report, Raman et al included one patient with a 4.5-cm kidney cancer mass [12]. Soon after, Kaouk et al reported a radical nephrectomy for a 5-cm left renal mass in their initial LESS series [40]. Subsequently, Ponsky et al described a LESS radical nephrectomy for an 8-cm renal tumor with intact specimen extraction [41].…”
Section: Opticsmentioning
confidence: 99%
See 2 more Smart Citations
“…In their initial report, Raman et al included one patient with a 4.5-cm kidney cancer mass [12]. Soon after, Kaouk et al reported a radical nephrectomy for a 5-cm left renal mass in their initial LESS series [40]. Subsequently, Ponsky et al described a LESS radical nephrectomy for an 8-cm renal tumor with intact specimen extraction [41].…”
Section: Opticsmentioning
confidence: 99%
“…[46,68] Slightly difficult Lack of specifically designed cryoprobes. High Simple nephrectomy [11,12,33,35,36,39,40] Fairly difficult Besides cosmetic advantages, other benefits for the patient still need to be fully demonstrated.…”
Section: 4mentioning
confidence: 99%
See 1 more Smart Citation
“…53 Three of the procedures were carried out with the umbilicus as the port of entry. All cases were completed uneventfully.…”
Section: Upper Urinary Tract Surgery (Table 6)mentioning
confidence: 99%
“…В 2007 г. A. Rane впервые сообщил об удалении поч-ки, произведенной однопортовым методом у взрос-лого пациента [12]. Позже Y.…”
Section: Discussionunclassified